The role of social-psychological support in breastfeeding promotion among young mothers: literature review - Handayani, Lina; Prihadi, Kussusanto Ditto; Vergawita, Tania; Fitriani, Isah; Hafidz, Beddu; Aisyahrani, Asa Ismia Bunga (International Journal of Public Health Science (IJPHS), 2025)
Breastfeeding promotion is vital for improving neonatal health and reducing mortality rates, particularly in developing countries. The World Health Organization advocates for exclusive breastfeeding during the first six months of life due to its substantial benefits for infant growth, development, and immunity. Understanding the determinants of exclusive breastfeeding, such as maternal knowledge and practices, is crucial for devising effective interventions to enhance breastfeeding rates among mothers. Social-psychological interventions, including family and peer support, have demonstrated efficacy in increasing breastfeeding frequency by addressing behavioral changes in new parents. Psychological factors such as self-efficacy, postnatal depression, and stress significantly influence breastfeeding decisions. Additionally, cultural norms, social media, and healthcare professionals are critical in shaping breastfeeding practices. This literature review examines the influence of these factors and interventions, underscoring the need for comprehensive strategies to promote breastfeeding, especially among novice and young mothers. Peer support programs, education-based initiatives, and postnatal support are highlighted as effective approaches. The study emphasizes the importance of tailored socio-psychological interventions and calls for further research to address existing gaps and strengthen the validity of findings, ultimately aiming to enhance breastfeeding outcomes and the overall well-being of mothers and infants.